Dreams from my father : a story of race and inheritance - Obama, Barack (New York : Three Rivers Press, 2004)
The son of an African father and white American mother discusses his childhood in Hawaii, his struggle to find his identity as an African American, and his life accomplishments.
Originally published: New York : Times Books, c1995. With new introd. and text from keynote address to the Democratic Convention, 2004.
Keywords: Obama, Barack. -- 1961 -; African Americans; Racially mixed people -- United States; Racism -- United States; United States -- Race relations